Six pairs of enantiomeric prenylated flavonoids with cytotoxic activities from Epimedium sagittatum Maxim - Shuang-Shuang Xie; Xiang Yu; Qi-Mei Tie; Jing-Ke Zhang; Bei-Bei Zhang; Meng-Nan Zeng; Xiao-Ke Zheng; Wei-Sheng Feng (Natural Products and Bioprospecting)
Abstract In this work, six pairs of undescribed enantiomeric prenylated flavonoids, ( ±)-epimesatines J–O (1a/1b–6a/6b), were isolated from the aerial parts of Epimedium sagittatum Maxim. Their structures and absolute configurations were determined based on spectroscopic data, quantum chemical calculations of electronic circular dichroism (ECD) and 13C NMR, as well as ECD experiments induced by Mo2(OAc)4 and Rh2(OCOCF3)4. The cytotoxicity assay revealed that compounds 1a/1b, 2a/2b, and 4a/4b–6a/6b demonstrated significant inhibitory effects on the viability of human breast cancer cells MCF-7 while exhibiting no obvious toxicity towards human breast epithelial cells MCF-10A. Additionally, these compounds were found to decrease the expression of sphingosine kinase 1 (Sphk1) in MCF-7 cells. Notably, compounds 4a and 5b exhibited IC50 values of 7.45 and 8.97 μM, respectively, in MCF-7 cells. Graphical Abstract